Burning mouth syndrome: a systematic review of treatments. (30th March 2017) - Liu, YF; Kim, Y; Yoo, T; Han, P; Inman, JC
Abstract : Burning mouth syndrome (BMS) is a chronic oral pain syndrome that primarily affects peri‐ and postmenopausal women. It is characterized by oral mucosal burning and may be associated with dysgeusia, paresthesia, dysesthesia, and xerostomia. The etiology of the disease process is unknown, but is thought to be neuropathic in origin. The goal of this systematic review was to assess the efficacy of the various treatments for BMS. Literature searches were conducted through PubMed, Web of Science, and Cochrane Library databases, which identified 22 randomized controlled trials. Eight studies examined alpha‐lipoic acid (ALA), three clonazepam, three psychotherapy, and two capsaicin, which all showed modest evidence of potentially decreasing pain/burning. Gabapentin was seen in one study to work alone and synergistically with ALA. Other treatments included vitamins, benzydamine hydrochloride, bupivacaine, Catuama, olive oil, trazodone, urea, and Hypericum perforatum. Of these other treatments, Catuama and bupivacaine were the only ones with significant positive results in symptom improvement. ALA, topical clonazepam, gabapentin, and psychotherapy may provide modest relief of pain in BMS. Gabapentin may also boost the effect of ALA. Capsaicin is limited by its side effects. Catuama showed potential for benefit. Future studies with standardized methodology and outcomes containing more patients are needed.